The poem "The Old Wound" by Mahmoud Darwish - a stylistic approach - Kebaili, Hamid; Ilyas, Lounas (Milev Journal of Research and Studies, 2023)
This study comes as a stylistic approach that seeks to identify one of the masterpieces of Mahmoud Darwish's poetry, the poem "The Old Wound", by examining the most important stylistic phenomena in it, and exploring the aesthetic dimensions in this poem, which belongs to the Diwan of "Late Night", as it falls within The first collections and poems of this stalwart poet, who used his poetry to convey the voice of the Palestinian cause, his pen was a sharp weapon in the face of the oppressor.